(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article examines the experience of the most advanced countries in the world in reforming, improving and improving the quality of higher education, active participation in global educational processes, the application of the best world practices in the development of higher education and the modular credit system.